Digital competence for students in the networking society 5.0: A systematic review - Wicaksono, Rudy Bagus; Prasetiyo, Wibowo Heru (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The systematic review provides research trends about the importance of digital competence among students in Indonesia. However, there are limited literature reviews regarding digital competencies for students. This research used the PRISMA protocol using Scopus, ERIC, and Google Scholar databases. Researchers set inclusion and exclusion criteria in the literature search. One hundred twenty-two articles were produced, which were then filtered to 20. This research used content analysis to code, classify, and develop themes. Based on the analysis results, three major themes were obtained: student digital competence, digital native students, and digital learning engagement. This review promotes the importance of digital competencies for students and recommends strategies for developing them through learning integration.